Rock-Eval Characteristic of Oligosen Fine-grained Sedimentary Rocks from Pamaluan Formation, Gunung Bayan Area, West Kutai Basin, East Kalimantan : Implication for Hydrocarbon Source Rock Potential - Moh. Heri Hermiyanto Zajuli; Joko Wahyudiono (Jurnal Geologi dan Sumberdaya Mineral, 2018)
In this study, we apply organic geochemistry analysis for evaluating source rocks in Gunung Bayan Areas, West Kutai Basin. Subject of this research are Oligocene fine-grained sedimentary rocks of Pamaluan Formation on Gunung Bayan Areas. The Oligosen fine-grained sedimentary rock of Pamaluan Formation consists of shale, siltstone and claystone. The organic geochemistry analysis includes pyrolysis data as total organic carbon(TOC%), generating source potential (S2), production index (PI), oxygen and hydrogen indices(OI, HI) and (Tmax). The results show that the Oligocene source rocks have poor into good quality with type III kerogen and have true capability to generate  gas. The source rocks candidate is  characterized by HI 5 - 115 (mg/g), TOC from 0.19 to 1.78 wt%, S1 from 0.01 to 0.09 (mg/g) and S2 from 0.05 to 1.74 (mg/g) that indicating poor to fair source rocks with type III kerogen and capable of generate  gas. The maturity of the fine-grained sedimentary rocks tend to indicate immature to mature stage. Overall fine-grained sedimentary rocks of Pamaluan Formation has capability to produced gas with poor to fair quality.